2012
DOI: 10.7150/ijbs.5147
|View full text |Cite
|
Sign up to set email alerts
|

Tube-Like Structures with Co-Expression of D2-40 and CD34: Newly Formed Vasculatures?

Abstract: Background: A great number of in vitro and in vivo studies have suggested that many pathways or factors can stimulate angiogenesis and lymphangiogenesis, which facilitate tumor progression and metastasis. However, the morphological and immunohistochemical profile of newly formed vasculatures has not been elucidated, making it difficult to differentiate them from the pre-existing ones, and to identify their unique molecular profiles for diagnosis and therapeutic interventions.Experimental findings: As cytokerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…More importantly, our studies have detected nearly identical focal capsule disruptions, lymphocyte infiltration, budding cell clusters, and the formation of TLCs in normal colorectal epithelial structures both distant from, and adjacent to, malignant lesions 65-66. Compared to their morphologically similar counterparts, node-positive CRC have the following unique alterations:…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…More importantly, our studies have detected nearly identical focal capsule disruptions, lymphocyte infiltration, budding cell clusters, and the formation of TLCs in normal colorectal epithelial structures both distant from, and adjacent to, malignant lesions 65-66. Compared to their morphologically similar counterparts, node-positive CRC have the following unique alterations:…”
Section: Introductionsupporting
confidence: 53%
“…In summary, this is a hypothesis paper, based on our previously published experimental data of studies in human breast and prostate tumors 26-37 and recent unpublished findings in human CRC 65,66. Our current study is the expansion of our previous studies with same concept and technical approaches.…”
Section: Implications Of Our Hypothesismentioning
confidence: 89%
“…Interactions between CSCs and tumor endothelial cells also play a major role in sequestering the angiogenic process as documented in brain cancer where Nestin + /CD133 + CSCs are located in direct proximity of endothelial cells. Considering the close association between CSCs and tumor endothelial cells, it has been proposed that newly formed vasculature within a growing tumor can be derived from the differentiation of CSCs implicating its multilineage differentiation capabilities …”
Section: Factors Governing Solid Tumor Heterogeneity and Csc Plasticitymentioning
confidence: 99%
“…MVD is a possible predictor of LNM in patients with CRC 31 . Another study showed that tube-like structures co-expressing D240 and CD34 were often observed at the junctions between preinvasive and invasive CRC 32 . Lymphatic vessels (LV and D240 positive) have been found even in the mucosa of in situ CRC, indicating the presence of a low tumor burden in regional LNs 33 .…”
Section: Discussionmentioning
confidence: 99%